2014
DOI: 10.1007/s10508-014-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Conflict-Related Sexual Violence Compared with Non-Sexual War Trauma in Female World War II Survivors: A Matched Pairs Study

Abstract: The aim of the study was to compare the long-term effects of conflict-related sexual violence experienced at the end of World War II (WWII) with non-sexual WWII trauma (e.g., being exposed to shell shock or physical violence). A total of 27 elderly wartime rape survivors were compared to age- and gender-matched control subjects who were drawn from a larger sample of subjects over 70 years of age who had experienced WWII-related trauma. A modified version of the Posttraumatic Diagnostic Scale was used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 29 publications
2
34
0
1
Order By: Relevance
“…(40) reported that sexual violence was associated with increased risk for lifetime PTSD and exposure to other traumas. Kuwert and colleagues (41) also reported that women exposed to conflict related sexual violence often exhibit more severe symptoms of PTSD than survivors of non-conflict sexual violence. Results of our univariate models showed an association between PTSD/CESD and sexual risk taking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(40) reported that sexual violence was associated with increased risk for lifetime PTSD and exposure to other traumas. Kuwert and colleagues (41) also reported that women exposed to conflict related sexual violence often exhibit more severe symptoms of PTSD than survivors of non-conflict sexual violence. Results of our univariate models showed an association between PTSD/CESD and sexual risk taking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established an association between sexual violence, posttraumatic stress disorder and sexual risk taking (68, 3741). Walsh et.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the literature outlined above (Brooks et al, 2018;Elderton et al, 2017;Kuwert et al, 2014), and the findings of our previous study (Anderson et al, 2019) a model of PTG was defined. The 6 core assumption is that the relationship between CRSV and PTG is mediated by psychosocial factors such as coping.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs particularly as a result of the difficulty in obtaining retrospective data in certain populations and a reliance on cross-sectional studies, and therefore an inability to make causal inferences (Cole & Lynn, 2010). Given the evidence, the most likely interaction is that events themselves do not result directly in PTG (Brooks et al, 2018), but individuals will respond to stress with a mixture of resiliencepromoting resources and vulnerability to mental illness (Kuwert et al, 2014; Shakespeare-Finch & Lurie-Beck, 2014)-a dual mechanism-rather than PTG falling on the 'adaptive' end of a single spectrum of post-trauma adjustment (Tedeschi & Calhoun,1996). This results in multiple indirect relationships between trauma, PTG and PTSD that may be impacted by psychosocial factors such as coping.…”
Section: Introductionmentioning
confidence: 99%